Polarized Z bosons from the decay of a Higgs boson produced in association with two jets at the LHC - Ezio Maina (SpringerOpen, 2021)
Abstract Investigating the polarization of weak bosons provides an important probe of the scalar and gauge sector of the Standard Model. This can be done in the Higgs decay to four leptons, whose Standard-Model leading-order amplitude enables to generate polarized observables from unpolarized ones via a fully-differential reweighting method. We study the $$\text {Z} $$ Z -boson polarization from the decay of a Higgs boson produced in association with two jets, both in the gluon-fusion and in the vector-boson fusion channel. We also address the possibility of extending the results of this work to higher orders in perturbation theory.